Green Infrastructure in Rural Development, Case Study in Hungary - Krisztina Filep-Kovács; Ágnes Sallay; Zsuzsanna Mikházi; Sándor Jombach; Zsolt Szilvácsku; István Valánszki; Géza Gelencsér (Fábos Conference on Landscape and Greenway Planning, 2016)
Green infrastructure (GI) planning as a complex, multifunctional tool is appropriate to realize objectives related to nature conservation, rural development, and sustainable agriculture. In a rural region of Hungary, we carried out a project covering wide range of activities: elaboration of new reservoirs, habitat rehabilitation enhancing the ecological stability of the Koppány-creek and suggestions for the improvement of the sustainability and multifunctionality of agricultural production. The pilot area is situated in Koppány Valley that is a hilly landscape rich in natural values located south of the popular tourist destination Lake Balaton and is affected by extreme aging and emigration processes. A rural development association emerged in the region to establish the Koppány Valley Nature Park. The association aims to develop innovative, sustainable tourism services based on natural values, to develop active recreational facilities, to strengthen local economy, and particularly to promote the diversification of agriculture and to create the social, economic and environmental sustainability of agricultural production. We elaborated a complex revitalization program in the frames of green infrastructure projects. Our green infrastructure development plan aims to develop the Koppány Valley natural capital: to increase the biodiversity and enrich the landscape. The green infrastructure project had the following objectives: ⎯ Elaboration of a complex analysis including economic, social and ecologic conditions, ⎯ Assessment of water management in the creek valley, ⎯ Assessment of functionality and connectivity of ecologic network, ⎯ Elaboration of a strategy for enhancing the ecologic value of the riparian vegetation and the surrounding landscape. ⎯ Elaboration of tourism development proposals based on the enhanced ecologic value of the region.
Keywords: greenways; green infrastructure; rural development; hungary